2001
DOI: 10.1509/jmkr.38.3.362.18861
|View full text |Cite
|
Sign up to set email alerts
|

Why Some New Products are More Successful than Others

Abstract: Product innovation is increasingly valued as a key component of the sustainable success of a business's operations. As a result, there has been a noticeable increase in the number of studies directed at explicating the drivers of new product success. To help managers and researchers synthesize this growing body of evidence, the authors conduct a meta-analysis of the new product performance literature. Of the 24 predictors of new product performance investigated, product advantage, market potential, meeting cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

43
1,055
4
19

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,155 publications
(1,151 citation statements)
references
References 61 publications
43
1,055
4
19
Order By: Relevance
“…This is consistent with prior research in the area of internet shopping which has shown that consumer intentions to search and buy online are most strongly affected by their utilitarian rather than their hedonic motivations (To, Liao and Lin, 2007). Given that two meta analyses have shown a weak correlation between product innovativeness and new product success (Henard and Szymanski, 2001;Szymanski et al, 2007), these results, which focus on consumer perception of innovativeness, emphasize the importance of understanding individual consumer behavior processes to evaluate innovations.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with prior research in the area of internet shopping which has shown that consumer intentions to search and buy online are most strongly affected by their utilitarian rather than their hedonic motivations (To, Liao and Lin, 2007). Given that two meta analyses have shown a weak correlation between product innovativeness and new product success (Henard and Szymanski, 2001;Szymanski et al, 2007), these results, which focus on consumer perception of innovativeness, emphasize the importance of understanding individual consumer behavior processes to evaluate innovations.…”
supporting
confidence: 88%
“…The study also is the first to show how affect is an important aspect of the innovation evaluation process. A better understanding of the consumer side of innovation may also help explain the somewhat inconsistent relationship between product innovativeness and new product success (Henard and Szymanski, 2001;Szymanski, Kroff, and Troy, 2007;Verdegem and De Marez, 2011). However, still the literature provides little consensus on how consumers perceive innovations (Garcia and Calantone, 2002), and specifically, little consensus on what innovativeness is, as rated by consumers.…”
mentioning
confidence: 99%
“…Drawing on the NPD literature in both traditional firm settings (for a metaanalysis, see Henard and Szymanski 2001) and the OSS domain (Grewal et al 2006, Lee et al 2009), 475 and recognizing the critical roles both subcommunities play, we propose three factors that influence OSS NPD process success: (1) the information and resources available to the project, which depend on the location of the project founders in the social network of developer users (Burt 1997, Lin 2001; (2) the interplay of the project's developer user and end user communities; and (3) the characteristics of OSS projects and the resulting products.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, (Cooper, et al, 2004) mentioned that ideas of top managers is significant in defining the time interval in presenting the new products and services (Cooper, et al, 2004). Applying the meta-analysis, Henard and Zimanski attempted to describe the factors which impact capability of organizations in order to present new products (Henard & Szymanski, 2001). In current research, the positive relationship among the support factors of top management and entrepreneurial activity of presenting new products was verified.…”
Section: Management Support and Cementioning
confidence: 77%